Design An Infant Warmer With Android-Based Temperature Monitoring - Lukman Medriavin Silalahi; Gunawan Osman; Freddy Artadima Silaban; Imelda Uli Vistalina Simanjuntak; Agus Dendi Rochendi (Journal of Informatics and Communication Technology (JICT), 2021)
Infant Warmer design testing or calibration with Android-based Temperature Monitoring is highly dependent on infant warmer modeling equipped with a microcontroller-based APGAR timer using 2 modes (water mode and skin mode) the timer can be activated by sound. The purpose of this research is to design an infant warmer tool with an Android-based temperature monitoring system using a research method consisting of several stages including the required voltage supply of AC 220V and dc voltage supply required by 5V, temperature setting in this Infant Warmer Design tool using temperature settings 36 - 37 °C , an effective distance of 8 meters of temperature monitoring, and a display on LCD devices and android apps. The result of this research is an infant warmer design module with Android-based monitoring and temperature monitoring with the application can work according to its function. The correction value measured in the temperature test was 33 °C at 0.16 °C, the temperature was 35 °C at 0.085 °C, the temperature was 37 °C at 0.1 °C, so the prototype could still be used. The relative percentage of errors is 0.2 % - 0.4% .from the comparison between kalibtor incu analyzer tools.